INTERPERSONAL NORMAL INDICATOR IN ESTABLISHING HEALTHY PSYCHOLOGICAL RELATIONSHIPS BETWEEN YOUNG BRIDE AND GROOM IN UZBEK FAMILIES - Rano ALIMARDANOVA (Scholar Express Journal, 2023)
According to the socio-psychological research conducted around the world, the number of divorces has increased in the last 30 years and it is sad that such situations are considered normal. One of the most important tasks for society is the effective use of socio-ethnic norms aimed at ensuring healthy psychological relationships in the family. One of the most important and effective solutions for this is the appropriate use of family psychotherapy.
Keywords: Family; psychological; relationship; daughter-in-law